2009
DOI: 10.1017/s0025315409003233
|View full text |Cite
|
Sign up to set email alerts
|

Using morphological and molecular tools to identify megalopae larvae collected in the field: the case of sympatric Cancer crabs

Abstract: Studies of recruitment dynamics in meroplanktonic organisms are dependent on the correct identification of each ontogenic stage of each species. This is particularly difficult when studying the larval stages, which are not easy to identify due to their lack of resemblance to conspecific adults and their high degree of similarity with congenerics at the same stage of development. This is the case with the crustacean megalopae of the genus Cancer along the coast of the south-eastern Pacific. This fact represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 37 publications
0
18
0
3
Order By: Relevance
“…Orensanz and Gallucci (1988) and DeBrosse et al (1990) found diVerences in size, appendage setation pattern, and timing of settlement in megalopae of C. magister from oVshore and inshore populations. Pardo et al (2009) recorded greater sizes in megalopae of C. setosus collected during the autumn as compared with those from spring collections. A similar pattern of seasonal size variation has been detected in other groups of decapods, such as anomuran megalopae (Gebauer et al 2007).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Orensanz and Gallucci (1988) and DeBrosse et al (1990) found diVerences in size, appendage setation pattern, and timing of settlement in megalopae of C. magister from oVshore and inshore populations. Pardo et al (2009) recorded greater sizes in megalopae of C. setosus collected during the autumn as compared with those from spring collections. A similar pattern of seasonal size variation has been detected in other groups of decapods, such as anomuran megalopae (Gebauer et al 2007).…”
Section: Introductionmentioning
confidence: 78%
“…Other traits such as rostrum shape and the hook-like spine on the isquium of chelipeds appear invariant, making them ideal as an "easy to locate" key character of identiWcation (e.g. Pardo et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of molecular markers has demonstrated to be a powerful tool in providing accurate identifications for plankton specimens (Pan et al 2008;Pardo et al 2009;Ampuero et al 2010;Marco-Herrero et al 2013a). The identification of megalopae has traditionally been based on morphological characteristics, but sometimes, it is impossible to get an accurate identification with this approach.…”
Section: Introductionmentioning
confidence: 99%